Co-Circulation of West Nile and Usutu Flaviviruses in Mosquitoes in Slovakia, 2018 - Čabanová, Viktória; Šikutová, Silvie; Straková, Petra; Šebesta, Oldřich; Vichová, Bronislava; Zubríková, Dana; Miterpáková, Martina; Mendel, Jan; Hurníková, Zuzana; Hubálek, Zdeněk; Rudolf, Ivo (Viruses, 2019)
Monitoring West Nile virus (WNV) and Usutu virus (USUV) activity now has the highest priority among mosquito-borne pathogenic viruses circulating in the European Union. This study documents a first time detection and the co-circulation of WNV lineage-2 (with the minimal prevalence of 0.46%) and USUV clade Europe 2 (with the minimal prevalence of 0.25%) in mosquitoes from the same habitat of south-western Slovakia and underlines necessity to perform rigorous surveillance in birds, mosquitoes, horses and humans in that country.
Keywords: Flavivirus Infections; komáří přenašeči; ptáci; Humans; Flavivirus; Birds; Phylogeny; West Nile Fever; West Nile virus; západonilská horečka; prevalence; Ecosystem; Culicidae; Horses; Female; Usutu virus; Public Health; virus západního Nilu; veřejné zdravotnictví; lidé; infekce viry z rodu Flavivirus; koně; zvířata; Culex; Culex spp.; Slovakia; Slovenská republika; mosquitoes; ženské pohlaví; Mosquito Vectors; fylogeneze; West Nile fever; surveillance; Prevalence; Animals; ekosystém